DEVELOPING AN ENGLISH LISTENING WORKBOOK FOR MULTIMEDIA DEPARTMENT OF VOCATIONAL HIGH SCHOOL - Dilla Sufianita (Jurusan Sastra Indonesia, 2019)
This study is aimed to develop listening supplementary materials in the form of a workbook for tenth grade students of multimedia department of vocational high school. This study used the research and development model adapted from Borg and Gall. The product developed that was validated by the expert validators included the workbook, answer key, tapescript and CD of the audio recording.